Isochoric heating and strong blast wave formation driven by fast electrons in solid-density targets. (4th October 2017) - Santos, J J; Vauzour, B; Touati, M; Gremillet, L; Feugeas, J-L; Ceccotti, T; Bouillaud, R; Deneuville, F; Floquet, V; Fourment, C; Hadj-Bachir, M; Hulin, S; et al.
Abstract: We experimentally investigate the fast ( < 1 ps ) isochoric heating of multi-layer metallic foils and subsequent high-pressure hydrodynamics induced by energetic electrons driven by high-intensity, high-contrast laser pulses. The early-time temperature profile inside the target is measured from the streaked optical pyrometry of the target rear side. This is further characterized from benchmarked simulations of the laser-target interaction and the fast electron transport. Despite a modest laser energy ( < 1 J ), the early-time high pressures and associated gradients launch inwards a strong compression wave developing over ≳ 10 ps into a ≈ 140 Mbar blast wave, according to hydrodynamic simulations, consistent with our measurements. These experimental and numerical findings pave the way to a short-pulse-laser-based platform dedicated to high-energy-density physics studies.